The effectiveness of virtual class-based e-learning with video-assisted google classroom as a physics learning media (2016-2020) - Irgy Redityo Dawana; Woro Setyarsih; Nadi Suprapto; Dwikoranto Dwikoranto (Momentum: Physics Education Journal, 2022)
This study aims to analyze research trends in online learning based on virtual class with video-assisted google classroom, the contribution of Indonesian researchers, and future research opportunities on the topic of online learning. This research method uses literature study through bibliometric analysis. In searching the articles, Publish or Perish (PoP) and Vosviewer softwares were utilized on the Scopus database. The search results consist of 264 documents selected from 2016 to 2020. The analysis results show that the publication of online learning articles with videos in the last five years has increased, which means that the research is still potential to be conducted. The most widely used author keywords in this research topic are "Video, Group, and Platform". Future research opportunities with the topic of online learning with videos in physics learning have potential opportunities where this study has increased every year and is still relevant for research.